2018
DOI: 10.3168/jds.2017-12694
|View full text |Cite
|
Sign up to set email alerts
|

Minimum inhibitory concentrations of frequently used antibiotics against Escherichia coli and Trueperella pyogenes isolated from uteri of postpartum dairy cows

Abstract: The objective of this study was to determine minimum inhibitory concentrations (MIC) of frequently used antimicrobials for Escherichia coli and Trueperella pyogenes isolated from postpartum bovine uteri of cows with acute puerperal metritis (APM, n = 67), cows suspected to have APM (n = 37), and healthy cows (n = 37) and to evaluate possible differences in MIC according to clinical signs. Cows with APM had reddish-brown, fetid vaginal discharge and rectal temperature (RT) ≥39.5°C within 21 d in milk; cows susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
6
25
1
Order By: Relevance
“…MICs of Trueperella pyogenes isolates were determined using the micro-dilution method in cation-adjusted Mueller Hinton broth (MHB), according to CLSI Guidelines [ 31 ]. Taking into account the growth characteristics of Trueperella pyogenes , MHB was supplemented with 2% (vol/vol) lysed horse blood [ 32 ]. The plates were incubated for 48 h in a CO 2 -enriched atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…MICs of Trueperella pyogenes isolates were determined using the micro-dilution method in cation-adjusted Mueller Hinton broth (MHB), according to CLSI Guidelines [ 31 ]. Taking into account the growth characteristics of Trueperella pyogenes , MHB was supplemented with 2% (vol/vol) lysed horse blood [ 32 ]. The plates were incubated for 48 h in a CO 2 -enriched atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of T. pyogenes isolation may differ, depending on a host species and a geographic region. The majority of published data concerns T. pyogenes infections in food animals and comes from Europe [21,33,34,35,36,37,38], China [39,40,41,42,43], Japan [44,45], Brazil [30,46], and the United States [47,48,49,50]. In livestock, the diseases caused by T. pyogenes generate significant economic losses, mainly in cattle and swine breeding, causing a reduction of meat and milk yield, as well as decreased reproductive efficiency and sometimes the necessity to cull diseased animals.…”
Section: Pathogenicitymentioning
confidence: 99%
“…In cattle, T. pyogenes mainly causes infections of the reproductive tract and the mammary gland, as well as pneumonia and liver abscessation. The most prevalent diseases in dairy cows related with this bacterium are metritis and endometritis, which may develop in a clinical form in about 23–52% of animals after parturition [29,32,38,39,66]. T. pyogenes together with many other bacteria comprises a vaginal biota of healthy cows [67], and may also colonize and persist in the uterus of dairy cows with normal puerperium [21,38].…”
Section: Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in Iran, the majority of T. pyogenes bovine isolates was susceptible to gentamicin (98.5%) while 33.8% were streptomycin-resistant [ 31 ]. Pohl et al [ 32 ] also observed a significant level of susceptibility to gentamicin (MIC 50 = 1 µg/mL and MIC 90 = 4 µg/mL) in T. pyogenes isolated from dairy cattle in Germany. On the other hand, a high percentage (84.4%) of streptomycin-resistant bovine T. pyogenes isolates was recorded in the study of Liu et al in China [ 5 ].…”
Section: Discussionmentioning
confidence: 98%